PROBLEM HUKUM ATAS KELEMBAGAAN DAN OPERASIONAL BANK SYARIAH - Rusnaena, Rusnaena (DIKTUM: Jurnal Syariah dan Hukum, 2014)
Islamic Bank in Indonesia is still very experienced legal problems because it is still plagued with some of the Banking Act that exist, so the Islamic Bank is not free to develop their products, these problems include institutional and legal problems of legal problems operational, operational and legal problems, among others, taxation problems as well as problems of liquidity management. Hence the need for affirmation of the law against such things. Islamic banks operating in Indonesia as a country of law, must be adapted to the provisions in force in the territory of Indonesia based on Pancasila and the Constitution of 1945. Similarly Islamic Bank in Indonesia also have to meet the requirements set by Bank Indonesia tela as in Indonesia's Central Bank issued the Banking Act.